PENGEMBANGAN PERANGKAT PEMBELAJARAN KIMIA BERORIENTASI MODEL AKTIF BERBASISINKUIRI (ABI) UNTUK PENINGKATAN LITERASI SAINS SISWA - Linda Rahmawulan; Muhali Muhali; Suryati Suryati (Universitas Pendidikan Mandalika Mataram, 2016)
Acid-base material and the salt is a chemical material first in the junior and considered difficult by students. In addition, students are less able to associate the material with any problems or phenomena in everyday life. The solution of this problem is to develop a learning device-oriented models based Active Inquiry (ABI). This study aimed to develop a learning device in the form of student activity sheet (LKS) oriented learning model based Active Inquiry (ABI) to improve scientific literacy in acid material bases and salts. This research was the development of the ADDIE model design consisting of five phases: (1) Analyze phase, (2) the define phase, (3) develop phase, (4) the stage of implementation, and (5) evaluation stage. Results of development validator validated by three experts, one validator practitioners, and using the instrument validation of a questionnaire, as well as small group trial to 10 students of class VIII SMPN 4 BatukliangNorth. Quantitative data validation results were analyzed by percentage formula. Qualitative data in the form of comments and suggestions for improvement of the validator was used as consideration to revise the learning device developed. Based on a questionnaire validated by expert appraisal to the learning device development results obtained by the average percentage of expert lecturers, teachers, practitioners, and testing a limited group * 83%, 94,28% and 96.46%. Test the effectiveness of products to increase scientific literacy using the formula N-gain obtained an average of 0.5 where improvement is average. Based on the results obtained, the learning device developed very decent tested in larger groups, and these devices can improve the scientific literacy of students.